Features of the Purposes Formation of the Education Management System - Aleksey I. Pykhtin; Olga V. Ignatyeva; Arkadiy N. Silenko; Marina V. Melnichuk; Anatoly I. Chernykh (International Review of Management and Marketing, 2016)
The article presents the analysis of purposes statement in higher education management. Currently, the ideas, about the economic education content, having received which, the person is able to continue to plan the career, are changing. The increasing recognition gets approach within which formation of key competences, design type of thinking, analytical skills, motivated aspiration to continuous self-education, self-improvement becomes the main objective of teaching and educational process that provides formation of competent experts with economic education and possibility of their further professional growth. Innovative processes in the economy in the last decade, stimulated in Russian society, the development of skills needs at all levels in the field of economy, capable of practical creative activity, initiative, enterprising, ready to solve non-standard tasks, problems and objectively analyzing the supply and demand in a market economy. The education management system objectives should be focused on addressing global psycho-pedagogical, didactic and methodological problems.